HUBUNGAN PERILAKU PERSONAL HYGIENE DAN STATUS KECACINGAN DENGAN STATUS GIZI ANAK SEKOLAH DASAR DI WILAYAH KERJA PUSKESMAS II SUMBANG - Arifin, Lida; Purnamasari, Dyah Umiyarni (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2018)
Background : Nutrition is one kind of important factors that build qualified human resources. A child being underweight due to two important things, they are food intake and illness. One type of infection that is often found in children that worm infection. The infection is often found in developing countries with lack of personal hygiene. The purpose of this research is to determine relation between personal hygiene and status worm infection with nutritional status among primary children.   Methods : This study design was observational analytic study with cross sectional approach. The sample were 51 children fourth grade 01 Banjarsari Kulon and 02 Banjarsari Wetan Primary School.   Results : Respondents with normal nutritional status 72%. Respondents with good behavior personal hygiene 59%. Respondents with positive helminthiasis status 53%. Relation between personal hygiene and nutritional status was examined by chi square (p value 1.000 > 0.05). Relation between helminthiasis status and nutritional status p value 0.425. Relation between personal hygiene and helminthiasis status p value 0.625.   Conclusion : There is no relation between the behavior of personal hygiene and nutritional status of school children in Puskesmas II Sumbang. There is no relation between helminthiasis status and nutritional status of school children in Puskesmas II Sumbang. There is no relation between personal hygiene and helminthiasis status.